Explaining the Ambiguity of Past-Under-Past Embeddings - Kauf, Carina; Zeijlstra, Hedde (Proceedings of the Amsterdam Colloquium, 2025)
Past-under-past embeddings have two readings, a simultaneous and a backward-shifted one. While existing accounts derive these readings via distinct mechanisms, be it by means of an ambiguity at the level of LF or via blocking of a cessation implicature, we propose an alternative account which avoids such ambiguity. For us, the meaning of a past tense morpheme, like-ed, is comprised of two components. Syntactically, every past tense morpheme carries an uninterpretable past feature [uPAST], to be checked by a (single) covert past tense operator Op-PAST carrying an interpretable feature [iPAST]. Semantically, the past tense marker encodes a relative non-future with respect to its closest c-commanding tense node (informally: ‘not later than’), immediately yielding the two distinct readings.